(untitled) (Texas Journal of Philology, Culture and History, 2024)
In this article, the importance of homonyms as a factor in the development of thinking, the methods of formation of homonyms, the creation of artistic arts based on homonyms, its direct connection with linguistic consciousness, thinking, perception, its importance in the development of thinking, and the phenomena of homonymy and polysemy, based on scientific sources peripherally based